Developmental Changes in the Inhibition of Glycinergic Synaptic Currents by Niflumic Acid in Hypoglossal Motoneurons - Petukhova, Elena; Ponomareva, Daria; Mukhamedyarov, Marat; Maleeva, Galyna; Bregestovski, Piotr (Frontiers in Molecular Neuroscience, 2018)
Mammalian brainstem hypoglossal motoneurones receive powerful synaptic glycinergic inputs and are involved in a variety of motor functions, including respiration, chewing, sucking, swallowing and phonation. During the early postnatal development, subunit composition of chloride-permeable glycine receptors (GlyRs) changes leading to a decrease of "fetal" alpha2 and elevation of "adult" alpha1 GlyR subunits. It has been recently demonstrated that niflumic acid (NFA), a member of the fenamate class of nonsteroidal anti-inflammatory drugs, is an efficient subunits-specific blocker of GlyRs. At a heterologous expression of different GlyR subunits it has been shown that blocking potency of NFA is more than one order higher for alpha2 GlyRs than for receptors formed by alpha1 subunit. To reveal the action of NFA on the synaptic activity we analysed here the effects of NFA on the glycinergic inhibitory postsynaptic currents in the hypoglossal motoneurones from mouse brainstem slices. In the whole-cell patch clamp configuration, the amplitude and the frequency of glycinergic synaptic currents from two age groups have been analyzed: "neonate" (P2–P4) and "juvenile" (P7–P12). Addition of NFA in the presence of antagonists of glutamate and GABA receptors caused a decrease in the mean amplitude and frequency of synaptic events. The degree of the inhibition induced by NFA decreased with the postnatal development, being higher on the motoneurons from "neonate" brainstem slices in comparison with the "juvenile" age group. Analysis of the pair-pulse facilitation suggests the postsynaptic origin of NFA action. These observations provide evidence on the developmental changes in the inhibition by NFA of glycinergic synaptic transmission, which reflects increase in the alpha1 and decrease in the alpha2 GlyR subunits expression in synapses to hypoglossal motoneurons during the early stages of postnatal life.